Financial Constraints vs Green Practices: Impact on Firm Value Energy in Indonesia - Saputra, Dian; Arifin, Zidan Dwinanda (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
The impact of eco-efficiency, asset turnover, green accounting, and financial limitations on business value in the energy industry on the Indonesia Stock Exchange is examined in this study for the years 2020–2022. SmartPLS 3 was used to analyze financial statement data from 52 energy sector companies using Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings indicate that while financial limitations have no discernible impact on corporate value, green accounting, asset turnover, and eco-efficiency do. The results of this study have significant implications for understanding the variables affecting business performance and value in the energy industry, as well as the significance of asset turnover, eco-efficiency measures, and green accounting in raising firm value. This research is expected to contribute to practitioners, regulators, and stakeholders in Indonesia's energy sector in the future to understand the influence of these factors.